Hubungan Pengetahuan Gizi Seimbang, Tingkat Kecukupan Energi dan Zat Gizi Makro terhadap Status Gizi Remaja Sman 1 Kota Cirebon - Annida Hanna Maula Azzahra; M. Duddy Satrianugraha Wahidin; Ali Manfaluthi Ahmad (KOLONI, 2026)
Nutrional status is an important factor in determining a person’s quality of life. Adolescents must be able to choose healthy foods and must understand that food is always related to nutritional status and also health. Problems that often occur in adolescents are overweight and underweight. This study aims to determine the relationship between balanced nutrition knowledge, energy adequacy and macronutrients to the nutritional status of adolescents of SMAN 1 Cirebon City.This study is an observational analytical study with a cross sectional method. The sample of this study totaled 168 people using consecutive sampling as a sampling technique. Knowledge data was collected using questionnaires and energy intake data and macro substances using a 24-hour food recall. In the multivariate statistical test of ordinal logistic regression, a significant relationship was found between the level of energy adequacy (p 0.003) and protein intake (p 0.010) on the nutritional status of adolescents.There was no relationship between balanced nutrition knowledge, carbohydrate intake and fat intake on adolescent nutritional status and there was a significant relationship between energy adequacy and protein intake on adolescent nutritional status.